The effectiveness of a collective guidance program using the time management and self-efficacy skills of the students of the Faculty of Applied Sciences (in Abri) in the Sultanate of Oman - Al - Ghafri, Nasra Muslim Hamad (Journal of Educational and Psychological Sciences, 2018)
The aim of this research was to investigate the effectiveness of a group counseling program using the time management and self-efficacy skills of the students of the Faculty of Applied Sciences in Baabri, and to determine whether there were significant differences in the average scores of the sample. , The semi-experimental approach was used to design a single group for an instructional program prepared by the researcher. The time and self-efficacy measures were also used. The results showed that there were statistically significant differences in the mean time of the sample of the sample for the time management measure, where the measurement was 3.13, The (4.04). The study also showed that there were statistically significant differences in the mean scores of the sample members before and after the implementation of the program for the self-perceived efficiency scale. The tribal measurement was (2.94), while the post measurement was (3.68) The study showed no statistically significant differences in the time management measure of the tribal and remote measures due to the gender variable. There were statistically significant differences in self-efficacy due to the gender variable in the post-measurement. There were also no statistically significant differences in time management and self-efficacy The dimension Due to the variable of the school year. In the light of the results of the study, some recommendations were made to activate the skills of time management and the self-efficacy of the students, including the opening of psychological counseling centers for specialists in the field for the work of many of the counseling programs at the faculties of applied sciences in the Sultanate. And the application of programs similar to students to improve their academic level and training in skills such as skills of self-confidence, self-assertion and other skills that contribute to the construction of the normal personality, the inclusion of curricula in touch with reality Social and practical students, the allocation of some student-friendly activities that contribute to the building of high self-efficacy for students, the work of seminars for academic counselors to raise awareness of students through them and encourage them to train those skills